Reninoma: An Uncommon Cause of Renin-Mediated Hypertension - Trnka, Peter; Orellana, Luisa; Walsh, Mark; Pool, Louis; Borzi, Peter (Frontiers in Pediatrics, 2014)
Reninoma (juxtaglomerular cell tumor) is a rare cause of renin-mediated hypertension. Reninomas are usually diagnosed in adolescents and young adults with occasional reports in younger children. Patients typically present with a long history of headaches leading to a diagnosis of severe hypertension that responds well to antihypertensive treatment targeting the renin-angiotensin-aldosterone system. The clue to clinical diagnosis is the presence of hypokalemia and metabolic alkalosis on the first blood sample drawn before any treatment is instituted. Elevated blood levels of renin and aldosterone confirm the clinical suspicion of renin-mediated hypertension. Diagnostic imaging is employed to identify the source of excessive renin production. While renal ultrasound can miss reninoma, contrast CT or MRI of the kidneys are diagnostic modalities of choice leading to the correct diagnosis. Renal vein renin sampling with lateralization might help to identify the site of excessive renin production. Nephron-sparing surgery is curative with maintenance of normal blood pressure after discontinuation of antihypertensive medications in the majority of patients. In this paper, we present the case of reninoma in an adolescent girl emphasizing clinical presentation, diagnostic evaluation, and medical and surgical treatment of this rare tumor. We also discuss important points in the management of children presenting with renin-mediated hypertension.